2017
DOI: 10.1007/s10195-017-0462-y
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar total disc arthroplasty: outdated surgery or here to stay procedure? A systematic review of current literature

Abstract: BackgroundThe purpose of this study was to summarize the available evidence about total lumbar disc replacement (TDR), focusing our attention on four main topics: clinical and functional outcomes, comparison with fusion surgery results, rate of complications and influence on sagittal balance.Materials and methodsWe systematically searched Pubmed, Embase, Medline, Medscape, Google Scholar and Cochrane library databases in order to answer our four main research questions. Effective data were extracted after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 73 publications
0
35
0
1
Order By: Relevance
“…Almost 500 000 spinal fusions are performed annually in the United States to treat degenerative disc disease and other spinal pathologies . While mostly successful, evidence suggesting that reduced segmental mobility may accelerate degenerative changes at adjacent levels has driven interest in motion‐preserving approaches, such as total disc arthroplasty (TDA) . This class of implants can allow for some degree of flexion/extension, lateral bending, and axial rotation between adjacent vertebrae .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 500 000 spinal fusions are performed annually in the United States to treat degenerative disc disease and other spinal pathologies . While mostly successful, evidence suggesting that reduced segmental mobility may accelerate degenerative changes at adjacent levels has driven interest in motion‐preserving approaches, such as total disc arthroplasty (TDA) . This class of implants can allow for some degree of flexion/extension, lateral bending, and axial rotation between adjacent vertebrae .…”
Section: Introductionmentioning
confidence: 99%
“…1 While mostly successful, 2 evidence suggesting that reduced segmental mobility may accelerate degenerative changes at adjacent levels [3][4][5] has driven interest in motion-preserving approaches, such as total disc arthroplasty (TDA). 6 This class of implants can allow for some degree of flexion/extension, lateral bending, and axial rotation between adjacent vertebrae. [7][8][9] The underlying premise is that this mobility produces a more natural kinematic and biomechanical environment in the adjacent vertebrae-that is, motion and load-transfer patterns that are closer to those occurring without an implant.…”
Section: Introductionmentioning
confidence: 99%
“…Because they cause decreased mobility, mechanical pain, and a reduction in the quality of life, they are one of the main causes of disability in the population. [1][2][3] In cases of surgical necessity and depending on the diagnosis, specialists may opt for simple direct decompression or direct or indirect decompression with arthrodesis or arthroplasty. 1,3,4 Recent studies have shown that the placement of interbody cages can increase the fusion rate and reduce the number of operations, since they increase biodynamic stability in the segment, in addition to allowing a greater correction of sagittal alignment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In cases of surgical necessity and depending on the diagnosis, specialists may opt for simple direct decompression or direct or indirect decompression with arthrodesis or arthroplasty. 1,3,4 Recent studies have shown that the placement of interbody cages can increase the fusion rate and reduce the number of operations, since they increase biodynamic stability in the segment, in addition to allowing a greater correction of sagittal alignment. [5][6][7] Lumbar interbody fusion can have three main approaches: anterior, lateral, and posterior.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely assumed that altered segment biomechanics are contributing factors for the development of adjacent segment degeneration . Unlike spinal fusion, TDA can maintain or restore motion of a spinal segment, thus adjacent segment degeneration may be alleviated . However, the structure and function of native disks are fundamentally different from those of cartilaginous interface joints such as knee and hip .…”
mentioning
confidence: 99%